Wilsonosiphonia gen. nov. (Rhodomelaceae, Rhodophyta) based on molecular and morpho‐anatomical characters. Issue 2 (21st February 2017) - Bustamante, Danilo E.; Won, Boo Yeon; Miller, Kathy Ann; Cho, Tae Oh
Abstract : Morphological, anatomical, and molecular sequence data were used to assess the establishment and phylogenetic position of the genus Wilsonosiphonia gen. nov. Phylogenies based on rbc L and concatenated rbc L and cox 1 loci support recognition of Wilsonosiphonia gen. nov., sister to Herposiphonia . Diagnostic features for Wilsonosiphonia are rhizoids located at distal ends of pericentral cells and taproot‐shaped multicellular tips of rhizoids. Wilsonosiphonia includes three species with diagnostic rbc L and cox 1 sequences, Wilsonosiphonia fujiae sp. nov. (the generitype), W. howei comb. nov., and W. indica sp. nov. These three species resemble each other in external morphology, but W. fujiae is distinguished by having two tetrasporangia per segment rather than one, W. indica by having abundant and persistent trichoblasts, and W. howei by having few and deciduous trichoblasts.